Clustered Regularly Interspaced Short Palindromic Repeats-Associated Proteins13a combined with magnetic beads, chemiluminescence and reverse transcription-recombinase aided amplification for detection of avian influenza a (H7N9) virus - Xu, Hongpan; Peng, Lijun; Wu, Jie; Khan, Adeel; Sun, Yifan; Shen, Han; Li, Zhiyang (Frontiers in Bioengineering and Biotechnology, 2023)
Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) and CRISPR-Associated Proteins (CRISPR-Cas) have promising prospects in the field of nucleic acid molecular diagnostics. However, CRISPR-based fluorescence detection technology is mainly hindered by proteins with conjugated double bonds and autofluorescence, resulting in high fluorescence background, low sensitivity and incompatible reaction systems, which are not conducive to automatic clinical testing. Chemiluminescence (CL) detection technology has been applied mainly owing to its greatly high sensitivity, as well as low background and rapid response. Therefore, we developed a rapid, ultrasensitive and economical detection system based on CRISPR-Cas13a combined with magnetic beads (MBs) and chemiluminescence (CL) (Cas13a-MB -CL) to detect Influenza A (H7N9), an acute respiratory tract infectious disease. The carboxyl functionalized MBs (MBs-COOH) were covalently coupled with aminated RNA probe while the other end of the RNA probe was modified with biotin. Alkaline phosphatase labeled streptavidin (SA-ALP) binds with biotin to form MBs composites. In presence of target RNA, the collateral cleavage activity of Cas13a was activated to degrade the RNA probes on MBs and released ALP from the composites. The composites were then magnetically separated followed by addition of ALP substrate Disodium 2-chloro-5-(4-methoxyspiro {1,2-dioxetane-3,2′-(5′-chloro) tricyclo[3.3.1.13,7]decan}-4-yl)-1-phenyl phosphate (CDP-star), to generate the CL signal. The activity of Cas13a and presence of target RNA was quantified by measuring the CL intensity. The proposed method accomplished the detection of H7N9 within 30 min at 25 °C. When combined with Reverse Transcription- Recombinase Aides Amplification (RT-RAA), the low detection limit (LOD) was as low as 19.7 fM (3S/N). Our proposed MB-Cas13a-CL was further evaluated to test H7N9 clinical samples, showing superior sensitivity and specificity.